Minimally Invasive Approaches to DIEP flap Harvest: A review of current data - Nores, Gabriela del Pilar Garcia; Kanchwala, Suhail (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2022)
Breast cancer is the most prevalent cancer in the female population. Autologous tissue is often used for reconstruction after mastectomy. The deep inferior epigastric (DIEP) flap is a favorite for breast reconstruction because it entails careful perforator dissection with less muscle destruction. Recently, minimally invasive techniques in DIEP flap harvest have increased in popularity but their complication rate and security profile may vary from one technique to another. The purpose of this review study is to evaluate and compare two minimally invasive surgical approaches to abdominal based free flap harvest: the transabdominal pre-peritoneal robotic assisted DIEP flap harvest and total extra-peritoneal laparoscopic DIEP flap harvest.
Keywords: minimally invasive; autologous breast reconstruction; diep flap; robotic diep; laparoscopic diep